A Memory-Theory Perspective of Country-Image Formation. Issue 2 (June 2016) - Lee, Richard; Lockshin, Larry; Greenacre, Luke
Traditional country-of-origin strategy in international marketing uses a country-image halo to cue beliefs about the country's products. With expansive trade globalization, domestic consumers are likely to have experience with foreign products but know little of the products' origin country. Thus, equally important as traditional theory is the question of whether product beliefs can imbue country image, but little is known of this reverse influence. If product beliefs can generalize into a favorable country image, a chain effect will then enable traditional country-of-origin effects to benefit the country's other products. In this study, the results of three surveys across two countries show that product beliefs can indeed influence country image. However, the influence weakens with increasing country familiarity and exists only when the product and country are congruent. Furthermore, the influence can operate outside of conscious awareness. The authors draw on the associative network theory of memory to explain their findings. This research improves the theoretical understanding of country- and product-image halo and provides the grounds for product and brand managers to work with government and tourist organizations for increasing mutual effectiveness.